'Playing the man, not the ball': targeting organised criminals, intelligence and the problems with pulling levers. (7th February 2020) - Rowe, Mike; Søgaard, Thomas Friis
ABSTRACT: In efforts to combat organised crime, police forces have adopted variations on the pulling levers approach to individuals and groups identified with gun crime, drug supply and other serious offences. Once identified, those individuals and their networks are targeted for interventions from criminal justice agencies and their partners. When levers are pulled, criminals find their lives made intolerable by the attentions of multiple agencies. Identifying the right people for this sort of attention and the quality and currency of police intelligence are, then, key concerns for such strategies. But the choice of levers, and their implications also raise some difficult questions. The law is explicitly applied differently to those associated with organised crime than to anyone else. This paper reviews evidence from two ethnographic studies, one of police officers in three police forces in England and Wales, the other from a third-party policing arrangement in the Danish night-time economy. We seek to understand the ways in which levers are understood and used, raising questions about the efficacy of pulling levers.